2015
DOI: 10.1615/int.j.uncertaintyquantification.2015011166
|View full text |Cite
|
Sign up to set email alerts
|

A Nonstationary Covariance Function Model for Spatial Uncertainties in Electrostatically Actuated Microsystems

Abstract: This paper presents a data-driven method of estimating stochastic models that describe spatial uncertainties. Relating these uncertainties to the spatial statistics literature, we describe a general framework that can handle heterogeneous random processes by providing a parameterization for the nonstationary covariance function in terms of a transformation function and then estimating the unknown hyperparameters from data using Bayesian inference. The transformation function is specified as a displacement that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…It is seen that this form of the displacement function differs from that in Eq. (3.2) only by a linear term and it can be shown that the resulting covariance function is identical under this modification [29,32]. The final formulation is given by: We also assign prior PDFs to the unknown parameters in order to obtain their poste-rior estimates using the generated datasets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is seen that this form of the displacement function differs from that in Eq. (3.2) only by a linear term and it can be shown that the resulting covariance function is identical under this modification [29,32]. The final formulation is given by: We also assign prior PDFs to the unknown parameters in order to obtain their poste-rior estimates using the generated datasets.…”
Section: Resultsmentioning
confidence: 99%
“…(32) for a given set of values for d, so that the resulting random process closely matches the actual, unknown process from which the dataset is derived. A thorough discussion of this procedure may be found in [29]. We use Bayesian inference to perform the model estimation, in which we first assign prior probability density functions (PDF) to the unknown parameters and then compute the posterior PDFs under the influence of the data.…”
Section: Modeling Spatially Varying Random Fieldsmentioning
confidence: 99%
“…where Φ = {α i , ν, φ, θ} is a set of unknown parameters in the Gaussian process and Pr(Φ) and Pr(Φ|d) are the prior and posterior distributions of Φ, respectively. If prior information about the distribution of the unknown parameters exists, it can be incorporated into the prior probability density functions (PDFs) of the corresponding unknown parameters [31]. Conversely, if prior information on the parameters is absent, the uniform PDFs in the certain range can be included.…”
Section: Gaussian Process Modelingmentioning
confidence: 99%
“…However, autocorrelated measurements are not necessarily from a stationary process. Recently, different models for various nonstationary processes have been proposed in many areas of measurement science (see [3][4][5][6]). For measurements from a nonstationary process, how to evaluate the corresponding uncertainties is a critical task.…”
Section: Introductionmentioning
confidence: 99%